Attribution of responsibility for sexual crimes beyond individual actors – construction of responsibility of offenders, victims and society in laypersons' explanations. Issue 3 (September 2019) - Kotanen, Riikka; Kronstedt, Johanna
This study analyses laypersons' explanations for sexual violence. It focusses on how the responsibility for sexual crimes is constructed and attributed, and moreover, what kind of effect this has on the attribution of blame. The research data consist of 105 opinion pieces published in the leading Finnish newspaper since the beginning of the 21st century. The theory-driven qualitative analysis utilises attribution theory and focusses on laypersons' interpretations and explanations for unusual acts and events deviating from social norms. Attribution theory is commonly utilised in relation to micro-level actors, the offender and the victim, whereas in this article, it is broadened to include also society as a macro-level actor. The analysis reveals that the construction of responsibility derives from (I) the chronological presentation and explanation of sexual crimes; especially (II) the causality attached to chronological phases, which emphasises the victim's actions prior to the crime; and (III) the construction of active female agency against male passivity or absence of the perpetrator. Moreover, blame is based on a combination of active agency, produced in the analysed explanations, and stereotypical features connected to female gender (e.g. rape myths).